Potencials of the powders of Lonchocarpus punctatus in the control of Sitophilus zeamais - Gonz?lez, Sayonara; Pino, Oriela; Herrera, Rafael Segundo; Valenciaga, Nurys; Fortes, Dayleni; S?nchez, Yaima (Cuban Journal of Agricultural Science, 2011)
Plants have different challenges from the environment and respond to them. These responses to the biotic and abiotic environment permit them a better distribution of the resources to grow, reproduce and defend. This work was performed with the aim of establishing the composition of secondary metabolites and the potentials of the powders of the structural organs of Lonchocarpus punctatus in the control of Sitophilus zeamais. A completely randomized design was used with four repetitions and the treatments were: fruits, leaf, stem and a negative control. For L. punctatus, the phytochemical screening showed the presence of ?-amino groups, triterpens/steroids and tannins. The stems were noteworthy by having higher presence. The treatment of best insect mortality values (P < 0.001), lowest emergences and lowest grain weight losses was that of the stem with values of 72.36, 31.79, and 9.68 %, respectively. Besides, L. punctatus showed repellent effect for all the structures. It can be concluded that the plant of L. punctatus has diversity in the composition of groups of secondary metabolites and it was outstanding the presence of ?-amino groups, triterpens/steroids and tannins in the stems. Apparently, one or some of these compounds are associated with the anti-insect effect on Sitophilus zeamais. Therefore, the stem of L. punctatus, applied as powder at 1%, is a potentially active product in presence of S. zeamais. Key words: secondary metabolites, anti-insect, Sitophilus zeamais.